Exploring global and local processes underlying alterations in resting-state functional connectivity and dynamics in schizophrenia - Metzner, Christoph; Dimulescu, Cristiana; Kamp, Fabian; Fromm, Sophie; Uhlhaas, Peter J.; Obermayer, Klaus (Frontiers in Psychiatry, 2024)
Introduction We examined changes in large-scale functional connectivity and temporal dynamics and their underlying mechanisms in schizophrenia (ScZ) through measurements of resting-state functional magnetic resonance imaging (rs-fMRI) data and computational modelling. Methods The rs-fMRI measurements from patients with chronic ScZ (n=38) and matched healthy controls (n=43), were obtained through the public schizConnect repository. Computational models were constructed based on diffusion-weighted MRI scans and fit to the experimental rs-fMRI data. Results We found decreased large-scale functional connectivity across sensory and association areas and for all functional subnetworks for the ScZ group. Additionally global synchrony was reduced in patients while metastability was unaltered. Perturbations of the computational model revealed that decreased global coupling and increased background noise levels both explained the experimentally found deficits better than local changes to the GABAergic or glutamatergic system. Discussion The current study suggests that large-scale alterations in ScZ are more likely the result of global rather than local network changes.